THE PRINCIPLE OF PARITY OF CULTURES AS A METHODOLOGICAL BASIS FOR WORKING WITH GOURNALISTIC TEXTS IN THE MGIMO - N. E. Merkish (Концепт: философия, религия, культура, 2017)
The article considers the principle of parity of cultures in its application to work with publicistic texts. Traditionally, the methodological basis is understood by the concepts and theories underlying the research. In the author's study, the principle of parity of cultures is the basis for working with the texts of the mass media and its theoretical ground. When teaching a foreign language in an institution of an international profile, the use of media texts is dictated by a number of factors, among which penetration of media into all spheres of foreign society's life is the main. In this way, the study of language and culture as professionally significant information for an international student becomes impossible without involving relevant media materials in the learning process. Working with these materials, one should use such an approach to perception and interpretation of media information that emphasizes the intercultural comparison of value systems, opinions and perceptions of the societies under consideration. Thus, the principle of parity of cultures is put at the center of the methodical system. This principle implies the equality of interacting cultures, in our case, the native culture of students and the culture of the country of the studied language. The principle of parity is based on the idea of egalitarianism or equality of cultures. This message assumes the need for a thorough analysis of incoming information, its critical comprehension in terms of priorities and values of both cultures. Therefore, "immersion" in the world of the studied culture allows not only to understand "someone else's" one, but also to look at your own culture differently, to rethink speech and behavioral stereotypes, to realize the value and depth of the acquired cultural tradition. We believe that the publicistic texts used in teaching process can be considered as the basis for mediated communication with native speakers who created them. As a result of this communication, the student perceives the information necessary to him, analyzes it and draws his own conclusions. As part of the process the principle of parity is realized: the active interaction of the two cultures, based on a critical comprehension of the arguments and logical constructions of the author-interlocutor. So, using the principle of parity of cultures as a methodological basis for working with publicistic texts provides an opportunity to teach MGIMO students an adequate assessment of media data. The result of this work is the assimilation of important cultural-specific and professionally relevant information, as well as the formed personal position on the issues discussed.